Fostering a Creativity Mindset for Teaching (and Learning) (LEARNing Landscapes, 2012)
Teaching is a creative practice that requires the kind of open-minded, whole-hearted, flexible, improvisational (yet knowledgeable), and performative orientation that I refer to as the "creativity mindset." Fostering such a mindset amongst preservice teachers can be challenging, since they often see their future teaching-selves as altruistic yet authoritarian subject matter experts. Underpinning these views are narrow conceptions of teaching, and of how we learn. To what extent can an experience of creative, performative pedagogy transform these views, and foster a creativity mindset for teaching (and learning) amongst preservice teachers?
Keywords: Teaching; creativity mindset; preservice teacher; pedagogy; creativity; learning